Influence of the work environment of nurses on the 30-day mortality of patients hospitalized in Polish hospitals. cross-sectional studies - Iwona Malinowska-Lipień; Dariusz Put; Michał Maluchnik; Teresa Gabryś; Maria Kózka; Krzysztof Gajda; Agnieszka Gniadek; Tomasz Brzostek; Allison Squires (BMC, 2024)
Abstract Background An optimal work environment for nurses is characterized primarily by appropriate staffing, good team relations, and support from the management staff. These factors are consistently associated with a positive assessment of patient safety by a hospital's employees and a reduction in hospital mortality rates. Aim To understand the relationships between the work environment as perceived by nurses on the 30-day mortality of patients treated in Polish hospitals. Background An optimal work environment for nurses is characterized primarily by appropriate staffing, good team relations, and support from the management staff. These factors are consistently associated with a positive assessment of patient safety by a hospital's employees and a reduction in hospital mortality rates. Material and methods The analysis used discharge data from 108,284 patients hospitalized in internal medicine and surgery departments in 21 hospitals (with 24/7 operations) in Poland. Administrative data included coded data to estimate 30-day mortality. A Nurses' satisfaction questionnaire, including the PES-NWI scale and the SAQ questionnaire, was used to assess the work environment of nurses (n = 1,929). Correlations between variables were assessed using the Pearson coefficient. The analysis used a Poisson regression model, which belongs to the class of generalized linear models. Results A lower 30-day mortality rate amongst patients was found among those treated in hospitals where the personnel feel that they may question the decisions or actions of their superiors regarding the care provided (r = − 0.50); nurses are informed about changes introduced on the basis of reports about negligence and mistakes (r = − 0.50); the ward nurse is a good manager (r = − 0.41); nurses receive timely information from the head of the department that may have an impact on their work (r = − 0.41). Conclusions Factors related to care during hospital stay such as the organization of care at the ward level, analysis of care errors, the number of staff providing direct patient care, informing nurses about mistakes without punishment, and the possibility of nurses challenging the decisions or actions of superiors, which concerns care providing, affect the 30-day mortality of patients after the end of hospitalization in Polish hospitals.